Changes in Neural Connectivity Underlie Decision Threshold Modulation for Reward Maximization - Green, Nikos (J Neurosci, 2012)
Using neuroimaging in combination with computational modeling, this study shows that decision threshold modulation for reward maximization is accompanied by a change in effective connectivity within corticostriatal and cerebellar–striatal brain systems. Research on perceptual decision making suggests that people make decisions by accumulating sensory evidence until a decision threshold is crossed. This threshold can be adjusted to changing circumstances, to maximize rewards. Decision making thus requires effectively managing the amount of accumulated evidence versus the amount of available time. Importantly, the neural substrate of this decision threshold modulation is unknown. Participants performed a perceptual decision-making task in blocks with identical duration but different reward schedules. Behavioral and modeling results indicate that human subjects modulated their decision threshold to maximize net reward. Neuroimaging results indicate that decision threshold modulation was achieved by adjusting effective connectivity within corticostriatal and cerebellar–striatal brain systems, the former being responsible for processing of accumulated sensory evidence and the latter being responsible for automatic, subsecond temporal processing. Participants who adjusted their threshold to a greater extent (and gained more net reward) also showed a greater modulation of effective connectivity. These results reveal a neural mechanism that underlies decision makers' abilities to adjust to changing circumstances to maximize reward.